Intraspecific drought tolerance in Ugandan Coffea canephora for accelerated breeding selection - Milton Ali; Settumba B Mukasa; Valerie Poncet; Godfrey Sseremba; Pierre Marraccini; Pascal Musoli; Daphne Nyachaki Bitalo; Hervé Etienne; Mildred Ochwo Ssemakula; Michael Kanaabi; Doreen Murenju Chelangat; Denis Fabre; et al. (PLoS ONE, 2026)
Robusta coffee (Coffea canephora ) accounts for about 80% of Uganda’s coffee production and supports over 2.2 million livelihoods. Yet recurrent droughts and erratic rainfall, exacerbated by climate change, pose severe threat to its productivity. Despite this threat, Ugandan breeding programs lack drought-tolerant varieties, largely because selection has not incorporated precise physiological traits linked to drought adaptation. Here, we evaluated 165 diverse Ugandan C. canephora genotypes, including local wild accessions, commercial lines, and breeders’ selections, under controlled screenhouse drought assay. Morphophysiological traits were collected before, during, and after drought stress. Using linear mixed-effects models, K-means clustering, and the Drought Factor Index, variation in drought tolerance was characterized across genotypes differing in biomass. Drought reduced water relations, gas exchange (gs and E), and PSII efficiency (Fv/Fm, Fo/Fv, ETR, Y(II), and PI) across all biomass groups. Nevertheless, 24 genotypes maintained higher DFI values, stable PSII function (Fv/Fm, PI, Fv/F₀), and less negative pre‑dawn water potential under severe stress. Among all traits, photosynthetic performance index (PI) and Fv/F₀ emerged as the most robust and biologically interpretable predictors of drought tolerance. These fluorescence‑based markers, together with the identified drought‑tolerant genotypes, provide a powerful foundation for accelerating climate‑smart coffee breeding in Uganda.